The Woof and the Warp of Architecture: The Figure-Ground in Urban Design - B.D. Wortham-Galvin (Footprint)
To borrow a metaphor used by Georg W.F. Hegel in the Philosophy of History to describe historical processes, architecture should be understood as a series of complex threads wherein one recognizes the physical forms as the warp, and the temporal, socio-political, natural, and aural contexts as the woof. Fabric is asserted as a concept broader than the immediate spatial and physical situation in which individual buildings are located; and, the threads of the fabric are all of those elements that aid in making the built environment both a designed and lived experience.